Dampened Inflammation and Improved Survival After CXCL5 Administration in Murine Lupus via Myeloid and Neutrophil Pathways. Issue 4 (22nd February 2023) - Fan, Xiubo; Ng, Chin Teck; Guo, Dianyang; Lim, Frances; Tan, Jia Chi; Law, Annie; Goh, Lim Hee; Poon, Zhi Yong; Cheung, Alice; Kong, Say Li; Tan, Michelle; Li, Shang; et al.
Abstract : Objective: To determine the efficacy of CXCL5 administration in lupus‐prone MRL/ lpr (Fas lpr ) mice and elucidate its working mechanisms. Methods: CXCL5 expression in blood (obtained from SLE patients and Fas lpr mice) and major internal organs (obtained from Fas lpr mice) was examined by Luminex, real‐time polymerase chain reaction, and immunofluorescent staining analyses. Pharmacokinetic studies were performed in Fas lpr mice and healthy Institute of Cancer Research mice. Efficacy of CXCL5 administration was demonstrated in Fas lpr mice, and the working mechanism of CXCL5 treatment was elucidated by flow cytometry, Luminex, and RNA sequencing. Results: In SLE patients, serum CXCL5 levels were significantly lower than in healthy individuals ( P < 0.0001) and negatively correlated with disease activity ( P = 0.004). In Fas lpr mice, disease severity progressed with age and was negatively associated with plasma CXCL5 levels. Intravenous administration of CXCL5 to Fas lpr mice restored endogenous circulatory CXCL5, improved mice survival, and reduced anti–double‐stranded DNA antibodies, proteinuria, lupus nephritis activity and chronicity indices, renal complements, and neutrophil extracellular traps over short‐term (10 weeks) and long‐term (2 years) time periods. In vitro and in vivo assays demonstrated that CXCL5 dictated neutrophil trafficking and suppressed neutrophil activation, degranulation, proliferation, and renal infiltration. Renal and splenic RNA sequencing further showed that CXCL5‐mediated immunomodulation occurred by promoting energy production in renal‐infiltrated immune cells, activating certain T cells, and reducing tissue fibrosis, granulocyte extravasation, complement components, and interferons. Further factorial design results indicated that CXCL5 appears to enhance host tolerability to cyclophosphamide in vulnerable individuals. Conclusion: We found that serum CXCL5 levels were significantly lower in SLE patients than in healthy individuals and were negatively correlated with disease activity. By administering CXCL5 intravenously in a mouse model of lupus, mouse survival improved, and indices of disease activity reduced significantly. Taken together, these findings indicate CXCL5 administration may represent a novel myeloid/neutrophil‐targeting therapy for SLE.